Effects of concentration of zinc dialkyldithiophosphate on the tribological properties of tetrahedral amorphous carbon films in presence of organic friction modifiers. (February 2016) - Okubo, Hikaru; Watanabe, Seiya; Tadokoro, Chiharu; Sasaki, Shinya
Abstract: The effects of the concentration of zinc dialkyldithiophosphate (ZDDP) on the tribological properties of a tetrahedral amorphous carbon (ta-C) film in the presence of organic friction modifiers (FMs) were investigated. Friction tests were conducted under lubrication with poly-alpha-olefin (PAO) and PAO containing glycerol-mono-oleate (GMO), tallow-diethanol-amine (TDEA), ZDDP, GMO+ZDDP, and TDEA+ZDDP. For PAO+GMO+ZDDP, the friction coefficients increased as the concentration of ZDDP increased. For PAO+TDEA+ZDDP, the ultralow friction was observed at the ta-C/ta-C contact regardless of the concentration of ZDDP. Surface analyses demonstrated the combination of TDEA and ZDDP promoting the formation of sulfur-rich tribofilms, which play important roles in the low friction of the ta-C film. Highlights: The frictional properties of the ta-C film depended on the combination of additives. The frictional properties of the ta-C film depended on the concentration of ZDDP. The ta-C film lubricated with PAO+TDEA+ZDDP showed an ultralow friction. The chemical composition of tribofilms depended on the combinations of additives. The high-sulfur rate tribofilm dominated an ultralow friction of the ta-C film.